PENGEMBANGAN MEDIA PEMBELAJARAN POP UP BOX BERBASIS CANVA PADA MATERI AKU BERPERILAKU PANCASILA UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA SEKOLAH DASAR - Maharani Balqis; Yuanita; Rifki Hanif Setiawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research began with the problem of low learning activity of second-grade students on the material "I Behave Pancasila" at SD Negeri 6 Tempilang. The factors causing this problem are the learning methods applied are still conventional and the lack of use of interesting learning media that can stimulate students to be active during the learning process. This research aims to produce a valid, practical, and effective Pop Up Box learning media product based on Canva in increasing student learning activity. The type of research used is development research (Research and Development) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of the study were 16 second-grade students of SD Negeri 6 Tempilang. Data collection techniques were carried out through observation, interviews, and questionnaires, which were then analyzed descriptively. The research shows that the Pop Up Box learning media based on Canva meets the eligibility criteria. Validation by media experts obtained a score of 80% (valid category) and by material experts 100% (very valid category). The practicality assessment by teachers was 95% and by students 98% (very practical category). Meanwhile, student learning engagement increased by 81% (very active) with an N-Gain of 0.438, categorized as moderate. Thus, the Canva-based Pop-Up Box media proved valid, practical, and effective in increasing second-grade elementary school students' engagement in the topic "I Behave in Pancasila."